Pengaruh Eco-Control, Environmental Performance, dan Corporate Social Responsibility terhadap Kinerja Keuangan perusahaan sub sektor makanan dan minuman di Bursa Efek Indonesia tahun 2019-2021 - Marcella Chandra; Apriansyah Ramadani; Violetta Nathalia; Gilbert Adryan Leonardo; Juli Meliza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test and analyse the effect of eco-control, environmental performance, corporate social responsibility on the financial performance of food and beverage sub-sector companies on the Indonesia Stock Exchange in 2019-2021. In the food and beverage sub-sector, since the pandemic took place until the beginning of 2021 it has still been able to consistently provide positive growth even though it is still limited and not too high. So far, environmental responsibility has been considered an ignored burden because companies have to incur certain costs to prevent environmental damage such as research costs on raw materials, waste management costs and so on. As a result, consumers do not get product satisfaction, excessive waste disposal and environmental conservation are not considered. The poor image of the company, which often appears in the mass media, clearly does not support the smooth operation of the company and is counter-productive to efforts to increase productivity and profits. It is now increasingly recognised that companies will not be able to continue to grow, if they do not care about the situation and conditions of the social environment in which the business runs. This research uses quantitative research with the sample used is 30 respondents. The data analysis method uses multiple linear regression. Purposive sampling was used as a sampling method. The conclusion of this study is that partially eco-control has a significant positive effect on financial performance, environmental performance has a negative and insignificant effect on financial performance, corporate social responsibility has a positive and insignificant effect on financial performance and eco-control, environmental performance, and corporate social responsibility together (simultaneously) have a positive and significant effect on financial performance. Keywords : Environmental Control, Environmental Performance, Corporate Social Responsibility, Financial Performance